A chemical conjugation of JQ‐1 and a TLR7 agonist induces tumoricidal effects in a murine model of melanoma via enhanced immunomodulation. Issue 2 (21st September 2020) - Wang, Xiaodong; Yu, Bingying; Cao, Birong; Zhou, Ji; Deng, Yongqiang; Wang, Zhulin; Jin, Guangyi
Abstract: In recent years, inhibitors of the BET bromodomain proteins, such as BRD4 inhibitors, have demonstrated robust antitumor activity. JQ‐1, a representative small molecular BRD4 inhibitor, is also effective to block PD‐1/PD‐L1 signaling by significantly decreasing the PD‐L1 expression on tumor cells. However, toxicity of BRD4 inhibitors on lymphoid and hematopoietic tissues limits their clinical usage. In this research, we designed and studied an immunogenic BRD4 inhibitor, SZU‐119, by coupling JQ‐1 with a TLR7 agonist, SZU‐101. In vitro, SZU‐119 stimulated the production of cytokines in mouse BMDCs and spleen lymphocytes, and inhibited the expression of PD‐L1 in mouse B16 tumor cells. In vivo, SZU‐119 suppressed the B16 tumor growth at both injected and uninjected sites, and prolonged the survival time of mice. SZU‐119 elevated the number of total CD8 + and IFN‐γ + CD8 + T cells in spleens, with greater CTL cytotoxicity to B16 tumor cells. It was also observed that the infiltration of CD8 + T cells was increased in tumors at both local and distant sites, and the PD‐L1 expression was decreased in tumor cells at the primary site. In conclusion, we have demonstrated that SZU‐119 activated the innate immune cells, kept efficacy of PD‐L1 blockade and abrogated immune toxicity, showing more potent antitumor effects than the simple mixture of SZU‐101 and JQ‐1 in a mouse melanoma model. Our work provides new insights for the development of anti‐melanoma drugs that concurrently target innate and adaptive immunity. Abstract : What's new? JQ‐1, a small‐molecule BRD4 inhibitor, blocks PD‐1/PD‐L1 signaling by decreasing PD‐L1 expression on tumor cells and increases the activity of antitumor cytotoxic T cells. However, the toxicity of JQ‐1 limits its clinical applications. Here, the authors coupled JQ‐1 with a TLR7 agonist to study whether concurrent activation of innate immune cells could enhance JQ‐1's efficacy. The novel immunogenic BRD4 inhibitor effectively activated innate immune cells, blocked PD‐1/PD‐L1 signaling, and abrogated immune toxicity, leading to enhanced antitumor effects in a mouse melanoma model. The work provides new insights for the development of anti‐melanoma drugs that concurrently target innate and adaptive immunity.